(untitled) (Eurasian Medical Research Periodical, 2023)
The immune status of children with recurrent bronchitis complicated by intestinal dysbacteriosis was studied. The role of intestinal dysbacteriosis in the formation of secondary immune deficiency, which mainly causes the development of relapses of bronchitis, has been established. The aim of the study was to study the role of intestinal dysbacteriosis in the formation of secondary immune deficiency in children with recurrent bronchitis. The data obtained showed that children with recurrent bronchitis complicated by intestinal dysbacteriosis have a deficiency of cellular and humoral immunity. In the stage of exacerbation of the disease, there were signs of intestinal dysbiosis II-III severity, in the remission stage of the disease I-II severity. Analysis of the quantitative and qualitative composition of the intestinal microflora in children with recurrent bronchitis showed a pronounced decrease in the content of bifidobacteria and lactobacilli. In children with recurrent bronchitis complicated by intestinal dysbacteriosis, a deficiency of cellular and humoral immunity was revealed